Education in Africa - Boukerroucha, Halima (2014)
The aim of this paper is to examine the education problems in Africa which include lack of proper schooling facilities and educators, emigration, military and conflict. Special reference is given to the most important problem that is educational systems of countries that do not serve the needs of today graduated students and make them not competitive. It tries to understand the causes behind Africa’s lowest index of educational development in the world as stated by the United Nations Development Programme (UNDP 2002) and the lack of reform in their educational systems. The paper attempts to suggest how NGOs should contribute most effectively to education development and how universities, governments, and NGOs might work together to strengthen (higher) education in Africa.